2019
DOI: 10.1111/ijac.13333
|View full text |Cite
|
Sign up to set email alerts
|

Ceramics based on calcium phosphates substituted with magnesium ions for bone regeneration

Abstract: In this study, chemical precipitation methods were used to obtain ceramic materials doped with magnesium ions in order to improve the regeneration properties of materials used for tissue engineering. Two different ratios of magnesium oxide were used to dope the ceramic powder, more precisely 5% and 10%. The synthesized materials were characterized to determine the calcination temperature of the precursor powder by means of thermal analysis; to determine the mineralogical composition, X-ray diffraction was empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The degradation of these ceramics in the body produces Ca 2+ and phosphate ions, which can promote new bone formation through bone induction. 157 Some metal ions, such as Sr 2+ and Zn 2+ , can inhibit osteoclast activity and enhance osteogenic activity. Therefore, these ions could be used to treat bone defects with osteoporosis.…”
Section: Treating Bone Defects Without Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of these ceramics in the body produces Ca 2+ and phosphate ions, which can promote new bone formation through bone induction. 157 Some metal ions, such as Sr 2+ and Zn 2+ , can inhibit osteoclast activity and enhance osteogenic activity. Therefore, these ions could be used to treat bone defects with osteoporosis.…”
Section: Treating Bone Defects Without Infectionmentioning
confidence: 99%
“…The degradation of these ceramics in the body produces Ca 2+ and phosphate ions, which can promote new bone formation through bone induction. 157…”
Section: Metal Ions-incorporated Different Carriers For Bone Repairmentioning
confidence: 99%
“…14 Mg 2+ plays a vital role in bones by maintaining healthy bone growth and providing a suitable environment for cell development. 15 To date, Most studies have concentrated on the effects of Mg doping on crystal morphology, structure, composition, phase, crystallinity, thermal stability, and sintering properties. However, the effect of the crystal structure from Mg doping and the subsequent sintering process on the degradation and bioactivity of Mg-HA bioceramic Mg-doped HAs (Mg-HAs) is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mg 2+ is related to the adhesion and growth of osteoblasts . Mg 2+ plays a vital role in bones by maintaining healthy bone growth and providing a suitable environment for cell development . To date, Most studies have concentrated on the effects of Mg doping on crystal morphology, structure, composition, phase, crystallinity, thermal stability, and sintering properties.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is a chemical dissolution reaction, where the entanglement of the crystals in the paste leads the self-setting of bone cement [ 12−14 ]. Moreover, recent studies have found that the proper release of magnesium ions during MPC degradation can enhance the bioactivity of osteoblasts [ 15 ]. Unfortunately, the ammonia emission during struvite preparation could restrict its clinical application range.…”
Section: Introductionmentioning
confidence: 99%